Relationship of Self-reported Attentional Fatigue to Perceived Work Ability in Breast Cancer Survivors. Issue 6 (November 2017) - Von Ah, Diane; Storey, Susan; Crouch, Adele; Johns, Shelley A.; Dodson, Jill; Dutkevitch, Sarah
Abstract : Background: Breast cancer survivors (BCSs) have identified attentional fatigue, a decrease in the ability to focus, as a persistent daily challenge; however, little is known regarding its impact on work ability. Objective: The purpose of this study was to examine the relationship between attentional fatigue and perceived work ability in BCSs controlling for the known covariates of age, education, household income, and time posttreatment. Methods: A cross-sectional, descriptive design was used. Breast cancer survivors who were currently employed and at least 1 year post–adjuvant treatment participated. Breast cancer survivors completed the Attentional Function Index and Work Ability Index questionnaires. Descriptive statistics, linear regression, and Fisher exact test were used for analysis. Results: Sixty-eight female BCSs, ranging from 29 to 68 years of age (mean, 52.1 [SD, 8.6]) and on average 4.97 (SD, 3.36) years posttreatment, participated. More than one-fourth of BCSs (26.5%) reported poor to moderate perceived work ability, indicating substantial concerns regarding work performance. Attentional fatigue was found to significantly predict perceived work ability ( P < .001), explaining 40% of the variance of perceived work ability. Conclusions: Attentional fatigue is a prevalent symptom posttreatment that is negatively related to perceived work ability in BCSs. Implications for Practice: Nurses are in a prime position to assess and intervene to alleviate attentional fatigue to improve work ability. Findings suggest a need for individual, comprehensive survivorship care plans to effectively address symptoms that impact work ability and, ultimately, the quality of life of cancer survivors.